The hobbit, or, There and back again - J. R. R. Tolkien (New York Del Rey, an imprint of Ballantine Books, 2014)
Bilbo Baggins, a respectable, well-to-do hobbit, lives comfortably in his hobbit-hole until the day the wandering wizard Gandalf chooses him to take part in an adventure from which he may never return